PROBLEMATIC ASPECTS OF THE USE OF URBAN UNDERGROUND SPACE IN INDONESIA - Hanny W Wiranegara (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2017)
Recently, the government is taking advantage of underground space for city’s infrastructure development needs. In fact, it is identified that the constraints are still remained in fulfilling the government mission. The aim of this paper is to reveal the problematic aspects in terms of the use of underground space by conducting qualitative data in term of interviewing experts and official staff of five local governments’ i.e.: Jakarta, Bandung, Surabaya, Makassar, and Medan. It is concluded that the problematic aspects are: the resources, land ownership, legal aspect; underground spatial planning, as well as technical and technological aspects. Keywords: underground space, utilization, problematic aspects